A label-free Acetone based SnO2 nanowire network sensor at room temperature - de Araújo, Estácio P.; Amorim, Cleber A. [UNESP]; Arantes, Adryelle N.; Chiquito, Adenilson J. (Springer Nature, 2022)
Acetone is a toxic gas employed in several pharmaceutical and commercial preparations, circumstances that demand efficient exposure control methods. Quasi-one-dimensional SnO2 (n-type) is a remarkable material for such purpose. In this work, we discuss the characteristics of an Acetone gas sensor built in a metal–semiconductor-metal (MSM) architecture, using a SnO2 nanowire network as an activity layer. The crystallographic information was confirmed using XRD and found out to be monocrystalline and in a rutile structure. SEM images confirmed that the desired nanowire morphology was obtained. The Acetone gas concentration was varied from 50 to 970 PPM and sensor response ranged between 9 and 32% at room temperature. By operating in 0.1 V, with a sensitivity of 49% in 970 PPM, an optimized regime of the gas sensor was achieved. The rise time varied between 8.7 s and 13 s and decay time ranged between 48.1 s and 142.7 s. In addition, we demonstrated fast response time, stability and reproducibility, all essential features for a high-quality sensor.
Keywords: Acetone gas sensor; Room temperature; SnO2 nanowire network